School Culture and Gender Equality: Principals’ Strategies in Realizing SDG 5 and Asta Cita 4 (Gender Equality) - Suciati, Sri; Munawar, Muniroh; Murphy, Susan P (Yayasan Keluarga Guru Mandiri, 2026)
Gender equality is more than just an issue in Indonesia and globally. In Indonesia, the government launched Asta Cita 4, while at the global level, the UN launched SDG 5. This study aims to describe principals' strategies in creating school cultures that promote gender equality, to achieve SDG 5 and Asta Cita 4 (gender equality). This study used a quantitative survey method. Data were collected via Google Forms using closed-ended questionnaires. The respondents were 177 principals, selected purposively. Data analysis was done with SPSS. The results reveal that there are four strategies of principals in creating school cultures that promote gender equality in realizing SDG 5 and Asta Cita 4: the role of principals in improving gender equality in education; school policies that support gender equality in education; teacher training on gender equality; and the implementation of gender equality in learning. This research concludes that the strategies can promote gender equality. This research’s contribution is to raise awareness of the significance of school cultures that promote gender equality, thus achieving Asta Cita 4 and SDG 5. Moreover, this study's results can serve as a guide for creating a school culture that supports gender equality in educational environments.